PENGARUH PENGETAHUAN PAJAK DAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA JAKARTA SAWAH BESAR SATU TAHUN 2023 - Komalasari, Nindi; Singgih, Rahadi Pratomo (Jurnal Ilmu Administrasi Publik, 2025)
This study discusses Tax Knowledge and Tax Audit. The purpose of this study is to analyze the effect of Tax Knowledge and Tax Audit on Taxpayer Compliance. The research method used is a quantitative approach. The population in this study were effective Taxpayers in 2023 at the Jakarta Sawah Besar Satu Tax Office. The population of individual taxpayers in 2023 was 1,101 Taxpayers. The number of samples in this study was 92. The data analysis methods used included instrument testing, classical assumption testing, and hypothesis testing. Based on the results of the study, it is known that Tax Knowledge has a significant effect with a t count of 6.396, Tax Audit has a significant effect with a t count of 2.772. The results of the F (Simultaneous) test show an F count of 20.274 with a significance value of 0.000 <0.05 so that the hypothesis of Tax Knowledge and Tax Audit on Taxpayer Compliance is accepted. The simultaneous effect is 31.3%.